2023
DOI: 10.3389/fgene.2023.1155199
|View full text |Cite
|
Sign up to set email alerts
|

Multiple epigenetic modification profiles reveal the tumor immune microenvironment and clinical outcomes of uveal melanoma

Abstract: Uveal melanoma (UM) is an aggressive intraocular cancer that, in 50% of cases, spreads to the patient’s other systems. The exact cause of the increased metastatic rate is still unknown. Methylation and immune response, metastasis, and the expansion of cancer cells are closely related. Additionally, proteins linked to RNA methylation have come to light as possible cancer treatment targets. However, the relationship between methylation-related genes (MRGs) and the tumor microenvironment (TME) is still not unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
1
0
0
Order By: Relevance
“…Our results showed that TIDE score was significantly lower in high-risk group, suggesting the better immunotherapy responsiveness in the high-risk group. These results were consistent with those of related study, and suggested that TIDE scores were higher in the low-risk UVM group (Nan et al 2023 ). On the contrary, bladder cancer patients in low-risk group were more sensitive to immunotherapy (Wu et al 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that TIDE score was significantly lower in high-risk group, suggesting the better immunotherapy responsiveness in the high-risk group. These results were consistent with those of related study, and suggested that TIDE scores were higher in the low-risk UVM group (Nan et al 2023 ). On the contrary, bladder cancer patients in low-risk group were more sensitive to immunotherapy (Wu et al 2022 ).…”
Section: Discussionsupporting
confidence: 93%